2022
DOI: 10.3390/cells11243993
|View full text |Cite
|
Sign up to set email alerts
|

SCAND1 Reverses Epithelial-to-Mesenchymal Transition (EMT) and Suppresses Prostate Cancer Growth and Migration

Abstract: Epithelial–mesenchymal transition (EMT) is a reversible cellular program that transiently places epithelial (E) cells into pseudo-mesenchymal (M) cell states. The malignant progression and resistance of many carcinomas depend on EMT activation, partial EMT, or hybrid E/M status in neoplastic cells. EMT is activated by tumor microenvironmental TGFβ signal and EMT-inducing transcription factors, such as ZEB1/2, in tumor cells. However, reverse EMT factors are less studied. We demonstrate that prostate epithelial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…Many studies have identified MZF1 as an oncogenic transcription factor [34,[37][38][39][40] and cancer stemness factor [41,42]. However, depending on the context, MZF1 can also function as a tumor suppressor [43][44][45]. While there are more than 50 types of SCAN-TFs, six zinc-fingerless SCAN domain-only proteins also exist [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have identified MZF1 as an oncogenic transcription factor [34,[37][38][39][40] and cancer stemness factor [41,42]. However, depending on the context, MZF1 can also function as a tumor suppressor [43][44][45]. While there are more than 50 types of SCAN-TFs, six zinc-fingerless SCAN domain-only proteins also exist [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…While there are more than 50 types of SCAN-TFs, six zinc-fingerless SCAN domain-only proteins also exist [30,31]. SCAND1 and SCAND2 (also known as SCAND2P) are SCAN domain-only proteins and can hetero-oligomerize with other SCAN-ZFs, including MZF1, through inter-SCAN domain interactions to repress transcription [32,33,37,43,46]. Thus, hetero-oligomerization between SCAN domain-only molecules and SCAN-ZF molecules can transform their roles, forming a transcriptional repressor complex [32,33,37,43,46].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations